PROBLEMATIKA SISTEM PENDIDIKAN INDONESIA - Sukari; Yoga Wicaksono; Warih Nurul Hidayati (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
The quality of education in Indonesia is currently very concerning. Education should pay attention to children's needs, not force something that makes children uncomfortable in seeking knowledge. A good education process is to provide opportunities for children to be creative. This must be done because basically children's thinking styles cannot be directed. In addition to the lack of creativity of educators in guiding students, a centralized curriculum makes the portrait of education increasingly blurry. The curriculum is only based on government knowledge without considering the needs of the community. Worse still, education is unable to produce creative graduates. Other causes of the low quality of education in Indonesia include problems of effectiveness, efficiency and standardization of teaching. This writing aims to describe the education system in Indonesia, describe the problems of education in Indonesia, and describe solutions that can be provided for problems of education in Indonesia. This study uses a descriptive qualitative method with data collection techniques through interviews, observations, and documentation. The education system in Indonesia is very dynamic in adapting to the times. Currently, Indonesia uses the 2013 curriculum which emphasizes character education.